2011
DOI: 10.1002/hipo.20777
|View full text |Cite
|
Sign up to set email alerts
|

The race to learn: Spike timing and STDP can coordinate learning and recall in CA3

Abstract: The CA3 region of the hippocampus has long been proposed as an autoassociative network performing pattern completion on known inputs. The dentate gyrus (DG) region is often proposed as a network performing the complementary function of pattern separation. Neural models of pattern completion and separation generally designate explicit learning phases to encode new information and assume an ideal fixed threshold at which to stop learning new patterns and begin recalling known patterns. Memory systems are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Signal noise may improve the learning by allowing the enhancement of those synaptic connections that occur in a spike timing dependent plasticity (STDP) manner. This synaptic modification is based on the concept that neuronal synapses are either strengthened or weakened depending on the temporal order of synaptic firing (Song et al, 2000; Taylor et al, 2009; Nolan et al, 2010). Theoretically by repeating a motor task such as stepping STDP reinforces or weakens selected sensorimotor synapses and results in a neural network functioning with less variability.…”
Section: Discussionmentioning
confidence: 99%
“…Signal noise may improve the learning by allowing the enhancement of those synaptic connections that occur in a spike timing dependent plasticity (STDP) manner. This synaptic modification is based on the concept that neuronal synapses are either strengthened or weakened depending on the temporal order of synaptic firing (Song et al, 2000; Taylor et al, 2009; Nolan et al, 2010). Theoretically by repeating a motor task such as stepping STDP reinforces or weakens selected sensorimotor synapses and results in a neural network functioning with less variability.…”
Section: Discussionmentioning
confidence: 99%
“…We will implement a full neural network model of the weighting algorithms. The conversion to a neural rather than mathematical model will provide access to beneficial neural computational processes such as "The Race to Learn", a process by which new sensory input is gradually learnt in a robust manner by a neural loop called the trisynaptic loop [27]. Such a process may provide a neurally-based method of implementing the autonomous threshold adjustment discussed previously.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Underpinning the capability of rats to flourish in such varied environments are a range of sophisticated neural functions that are performed in a brain region called the entorhinal-hippocampal formation, which consists of the entorhinal cortex (EC) and hippocampus [27]. These brain regions are thought to be involved in a number of critical functions; sensor fusion, variable pattern discrimination to suit perceptually distinctive or bland environments and detection of inconsistent sensory input through pattern completion.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that one way to encode the phase target is by locking the stimulus timing to the phase target (Figure 9). While we did not model the learning process that may perform this phase encoding, previous models have demonstrated encoding and recall in theta-modulated networks (Jensen et al, 1996; Wallenstein and Hasselmo, 1997; Hasselmo et al, 2002; Igarashi et al, 2007) using timing-based learning rules such as STDP (Lengyel et al, 2005; Câteau et al, 2008; Nolan et al, 2010). Additionally, our demonstration of stimulus timing-based phase-code retrieval using a spiking oscillator showed that effective encoding may rely on producing a stimulus representation with a trailing hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%